Management of Public Health Policy: Female Migrants in a Patagonian City, Argentina - Barria Oyarzo, Carlos (2020)
This work seeks to characterize the daily management of public health policy that targets women migrants from rural Bolivia in a city in Patagonia, Argentina. The fieldwork was carried out between 2016 and 2018 in two primary health care centers, located in periurban neighborhoods of the city of Comodoro Rivadavia, through accompanying the daily tasks of health agents, meetings, conversations and interviews with professionals, officials and migrant women. A focused and protective policy regarding the health of migrants was found, one that obscures a gendered, ethnic, social class and generational reading justifying control and subjectivation techniques, which in some cases are disputed. From an ethnographic perspective, contributions from the anthropology of health, the anthropology of the State and an intersectional gender perspective are able to identify the production and management of risk, as well as tensions created in contexts of inequality.